Pest control treatments with phosphine and controlled atmospheres in silo bags with different airtightness conditions. (October 2016) - Carpaneto, Bárbara; Bartosik, Ricardo; Cardoso, Leandro; Manetti, Pablo
Abstract: The silo bag technology has been extensively used in Argentina for storing grains (e.g. wheat, corn, barley, sunflower and soybean among others) since the mid-1990s. Silo bag are widely considered a hermetic storage system in which PH3 fumigation is frequently implemented for pest control. However, there is insufficient information regarding the potential airtightness of silo bags and how it could affect the performance of fumigation and controlled atmosphere treatments. In this study, a pressure decay test (PDT) was implemented to characterize airtightness level of silo bags set up following various procedures. PH3 fumigation treatments with different dosages and hermeticity levels were conducted, and fumigant concentration was monitored. Controlled atmosphere treatments with carbon dioxide were also implemented in silo bags with different hermeticity levels. Results showed that less than half of the bags tested in the field had a PDT indicated for fumigation (90 s), and that when a bag without thermo sealing was used for fumigation, this treatment failed. However, it was demonstrated that with simple and inexpensive practices silo bags can achieve high enough airtightness conditions to implement successful PH3 fumigation (5 days above 200 ppm with a dosage of 1 g of PH3 /m 3 ) and even controlled atmosphere treatments (more than 18 days with CO2 concentration above 70%). This study shows that silo bags could be used as a cost competitive hermetic storage technology for performing controlled atmosphere treatments. Highlights: Typical airtightness level of silo bags were characterized with a pressure decay test. Airtightness condition, fumigant dosage and treatment performance were evaluated. Sealing the end of silo bags is critical for successful fumigation. CA treatment (CO2 ) in silo bags was successfully implemented.